IMPLEMENTATION OF LEARNING MANAGEMENT SYSTEM (LMS) FOR TECHNICAL TRAINING IN THE EMS COMPANY - Arif Rahman Hakim; Sri Langgeng Ratnasari; Amrizal Amrizal; Missyamsu Algusri; Dadang Redantan; Fardin Hasibuan; Rosdiana Rosdiana (JURNAL EDUSCIENCE, 2026)
Purpose – This study was conducted in an electronics manufacturing company that was just starting the implementation of the Learning Management System (LMS) for the technical training subject. The LMS project started in September 2025.Methodology – This study used a literature review, observation, data collection, and a respondent survey. Several journals were reviewed to gather information from prior studies and research on this topic. Observations were also conducted to support the analysis. To understand employees' perceptions of the impact of LMS, several respondents were selected for a survey.Findings – 1) Accessibility of employees to the LMS is 98.56%. On average, it takes less than 1 minute for employees to access the LMS. 54.07% of surveyed employees stated that the LMS used by PT. PCBAI is very good and very helpful.  2) The effectiveness of the training activity is indicated by the increment of 18.4% of participants. The average final score on the post-test increased by 7.90%, from 90.39 to 97.53.  3) Participants' feedback on the learning experiences using the LMS Survey result showed that 99.04% respondents agree that the LMS is flexible and easy to access, 99.52% respondents agree that the LMS is practical. 4) The level of participants' satisfaction with the LMS. Survey results also show that 99.22% of respondents are very satisfied with the LMS implementation for their training needs. 5) The Role of Learning Management System (LMS) in Training Activities. 6)    Urgency of applying the Learning Management System (LMS) in training activities.Contribution – This study enhances management's confidence in implementing LMS in the organization and convinces management to support this implementation. It has been proven that the LMS is a suitable application for improving training activities.